2019
DOI: 10.1111/jan.13969
|View full text |Cite
|
Sign up to set email alerts
|

The role of professional commitment in improving nurses’ professional capabilities and reducing their intention to leave: Two‐wave surveys

Abstract: Background: Social cognitive career theory (SCCT) can explain the mechanism underlying the formulation of nurse turnover intention. However, little is known about the role of professional commitment in such a mechanism.Aims: The aim of this study was to explore how elements of SCCT have an impact on the three aspects of professional commitment and thus nurses' intention to leave the profession.Design: This study used surveys to collect two-wave data. Methods:The participants were sampled in all available units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 46 publications
0
52
0
1
Order By: Relevance
“…There is increasing acknowledgement of the significance and value of guiding nurses to fully realize the benefits of their careers and of improving NPPB in practice. Empirical research has identified significant associations among NPPB, willingness to stay [21], job burnout [21], subjective well-being [22], innovative behavior [23], work engagement [24], professional commitment [25], and sense of calling [26].…”
Section: Implications For Nursingmentioning
confidence: 99%
“…There is increasing acknowledgement of the significance and value of guiding nurses to fully realize the benefits of their careers and of improving NPPB in practice. Empirical research has identified significant associations among NPPB, willingness to stay [21], job burnout [21], subjective well-being [22], innovative behavior [23], work engagement [24], professional commitment [25], and sense of calling [26].…”
Section: Implications For Nursingmentioning
confidence: 99%
“…Professional commitment is beneficial for the employer and the employee. While professional commitment increases job satisfaction, it decreases work stress and intention to leave (Chang et al, ; Khamisa et al, ; Lu, Zhao, & While, ; Rudman, Gustavsson, & Hultell, ).…”
Section: Introductionmentioning
confidence: 99%
“…SCCT could explain career choices and career interest among hospital nurses (Chang, Lee, et al, ). To better connect to the SCCT literature, we chose to use the term ‘career interest’.…”
Section: Discussionmentioning
confidence: 99%